Analisis Penerapan Kebijakan Full Day School Terhadap Hasil Belajar Siswa Kelas X Di MAN 1 Surakarta - SEFTIANA, SEFTIANA; , Suranto, S.Pd., M.Pd (2017)
The purpose of this research are: (1) to describe how the implementing of policy full day school in effort to increase students learning achievement, (2) to describe support factor and unsupport factor implemented of policy full day school, (3) to describe how the role of full day school policy toward students learning achievement. The kind of this research is qualitative research. Technique of data analysis with reduction data, drawing data, and conclotion data. The validity of the data by triangulation technique that with compared interview data, observation and documentation. The result of the research show that: (1) implementing of full day school policy in MAN 1 Surakarta is K-13 curriculum which develop become laborat basic, (2) support factor there are any selection system high SDM and interaction with society, (3) unsupport factor laboratory is not yet available for social (IPS) class, less the classroom and remembering schedule until afternoon, so made tired and lessfocuss although teacher eventhough students, (4) implementing of full day school policy have important role in increasing students learning achievement.